2020
DOI: 10.1159/000505132
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide-Induced Depression-Like Behaviors Is Ameliorated by Sodium Butyrate via Inhibiting Neuroinflammation and Oxido-Nitrosative Stress

Abstract: Depression is a common disease that afflicts one in 6 people. Numerous hypotheses have been raised in the past decades, but the exact mechanism for depression onset remains obscure. Recently, the neuroinflammatory response and oxidative stress are being attracted more and more attention due to their roles in depression pathogenesis. The inhibition of neuroinflammatory response and oxidative stress is now considered a potential strategy for depression prevention and/or therapy. Sodium butyrate (SB) is a sodium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…In our study, LPS administration elicited a remarkable decrease in BDNF expression in the brains of mice. These results were in line with previous studies [26, 28, 29], which confirmed the connection among the pro-inflammatory cytokines, oxidative stress, and BDNF signaling. However, the exact mechanism of how CA affects the BDNF signaling is still unknown.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, LPS administration elicited a remarkable decrease in BDNF expression in the brains of mice. These results were in line with previous studies [26, 28, 29], which confirmed the connection among the pro-inflammatory cytokines, oxidative stress, and BDNF signaling. However, the exact mechanism of how CA affects the BDNF signaling is still unknown.…”
Section: Discussionsupporting
confidence: 93%
“…Neuroinflammation, defined as the cellular and biochemical responses to numerous insults that occur within the CNS 12 , has been shown to be highly involved in depression 47 . In the CNS, NLRP3 was found in microglial 48 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it was revealed that TNF-α and IL-6 levels might be negatively correlated with cognitive function ( 82 ) and blocking of the IL-6 signaling pathway reduced cognitive flexibility ( 83 ). SCFAs could inhibit fructose-induced hippocampal neuronal inflammation and neuronal loss in mice ( 32 ) and inhibit a neuroinflammatory response ( 84 ). Liu et al.…”
Section: Discussionmentioning
confidence: 99%